Demographic parameters of cowpea aphids on advanced semi-erect cowpea lines - Silva, Leandro Carvalho da; Nere, Daniel Rodrigues; Bleicher, Ervino; Barbosa, Antônio Vinícius Correa; Tavares, Eraldo José Madureira (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the resistance of advanced semi-erect cowpea (Vigna unguiculata) lines, by means of a screening assay for resistance and the elaboration of fertility-life tables of Aphis craccivora (Hemiptera: Aphididae). The experiments were carried out in a screenhouse. For the resistance trial, 15 advanced cowpea lines were used, as well as two standard genotypes for resistance and two for susceptibility, which were arranged in six blocks. After resistance was determined, two lines with the highest and lowest resistance were selected for the development of the fertility-life tables which were used to estimate demographic parameters. The MNCO4-762F-03 and MNCO4-762F-09 cowpea lines were classified as resistant, for which cowpea aphids showed the lowest values (in parentheses, respectively) for: net reproductive rate (RO = 3.0 and 2.5), intrinsic rate of increase (rm = 0.16 and 0.15), and finite rate of increase (λ = 1.18 and 1.16). The highest values were obtained for the 'Vita-7', MNCO4-795F-168, and 'BRS Tumucumaque' genotypes. The MNCO4-762F-03 and MNCO4-762F-09 lines show antibiosis-type resistance, which directly affects the reproductive potential of the cowpea aphid population.
Keywords: Aphis craccivora; Vigna unguiculata; fecundity; plant health; plant resistance